2017
DOI: 10.1007/s00284-017-1203-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Detoxification of Arsenic Under Carbon Starvation: A New Insight into Microbial Arsenic Physiology

Abstract: Nutrient availability in nature influenced the microbial ecology and behavior present in existing environment. In this study, we have focused on isolation of arsenic-oxidizing cultures from arsenic devoid environment and studied effect of carbon starvation on rate of arsenite oxidation. In spite of the absence of arsenic, a total of 40 heterotrophic, aerobic, arsenic-transforming bacterial strains representing 18 different genera were identified. Nineteen bacterial species were isolated from tannery effluent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…In H. arsenicoxydans, the expression of genes in the aio operon is related to the presence of AsIII and to the expression of genes involved in motility [38]. Our results are in accordance with those of Nandre et al [24], who observed a higher expression of aioA genes under acetate starvation condition in seven strains belonging to different genera, for one single time of incubation (8 h), in presence of 1.33 mM of As. Here, the phenomenon was observed with a complex organic substrate (yeast extract) and correlated with early growth phase.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In H. arsenicoxydans, the expression of genes in the aio operon is related to the presence of AsIII and to the expression of genes involved in motility [38]. Our results are in accordance with those of Nandre et al [24], who observed a higher expression of aioA genes under acetate starvation condition in seven strains belonging to different genera, for one single time of incubation (8 h), in presence of 1.33 mM of As. Here, the phenomenon was observed with a complex organic substrate (yeast extract) and correlated with early growth phase.…”
Section: Discussionsupporting
confidence: 92%
“…Several hypotheses may explain the negative effect of organic substrates on aioA gene expression and the bacterial specific AsIII-oxidation rate. Nandre et al [24] hypothesized cross protection in the carbon starvation stress wherein nutrient deprived cells show higher resistance against other stresses. However, this phenomenon could hardly explain results obtained with bacteria such as "T. arsenivorans" usually growing in mineral or oligotrophic media.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the addition of 3-/4-HBA delayed As(III) oxidation by strain H7. It has been reported that bacterial As(III) oxidation is related to the available carbon sources and that carbon starvation could enhance bacterial As(III) oxidation (Nandre et al, 2017; Lu et al, 2018). 1/10 ST medium is a nutrient poor medium, and 3-HBA and 4-HBA could serve as carbon sources.…”
Section: Discussionmentioning
confidence: 99%
“…Once arsenic enters into the human body, the skin, the cardiovascular systems, the nervous system, the kidney and the liver will be injured significantly. When the concentration of arsenic in the human body is 0.01–0.052 g, it will lead to arsenic poisoning; when the concentration of arsenic is 0.06–0.2 g, it will lead to death (Zeng et al 2017 ; Nandre et al 2017 ; Mukherjee et al 2017 ; Kempahanumakkagari et al 2017 ). Arsenic was considered as the priority controlled pollutants by World Health Organization (WHO) (El-Moselhy et al 2017 ; Miroslav et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%